Evaluation of the Whole Proteome of Achromobacter xylosoxidans to Identify Vaccine Targets for mRNA and Peptides-Based Vaccine Designing Against the Emerging Respiratory and Lung Cancer-Causing Bacteria - Khan, Taimoor; Abdullah, Muhammad; Toor, Tayyba Fatima; Almajhdi, Fahad N.; Suleman, Muhammad; Iqbal, Arshad; Ali, Liaqat; Khan, Abbas; Waheed, Yasir; Wei, Dong-Qing (Frontiers in Medicine, 2022)
Achromobacter xylosoxidans is a rod-shaped Gram-negative bacterium linked with causing several infections which mostly includes haematological malignancies. It has been recently reported to be associated with the development and progression of lungs cancer and is an emerging respiratory disease-causing bacterium. The treatment of individuals infected with A. xylosoxidans bacteremia is difficult due to the fact that this pathogen has both intrinsic and acquired resistance mechanisms, typically resulting in a phenotype of multidrug resistance (MDR). Efforts are needed to design effective therapeutic strategies to curtail the emergence of this bacterium. Computational vaccine designing has proven its effectiveness, specificity, safety, and stability compared to conventional approaches of vaccine development. Therefore, the whole proteome of achromobacter xylosoxidans was screened for potential vaccines targets characterization through subtractive proteomics pipeline for therapeutics design. Annotation of whole proteome confirmed three immunogenic vaccine targets (E3HHR6), (E3HH04) and (E3HWA2) which were used to map putative immune epitopes. The shortlisted epitopes specific against Cytotoxic T Lymphocytes, Helper T-cell Lymphocytes and linear B-Cell were used to design mRNA and multi-epitopes vaccine (MEVC). Initial validations confirmed the antigenic and non-allergenic properties of these constructs followed by docking with the immune receptor TLR-5 which resulted in robust interactions. The interaction pattern followed in the docking complex included formation of 5 hydrogen bonds, 2 salt bridges and 165 non bonded contacts. These stronger binding affinity was also assessed through using mmGBSA approach showing a total free binding energy of -34.64 kcal/mol. Further validations based on in silico cloning revealed CAI score of 0.98 and optimal percentage of GC contents (54.4%) indicated putative higher expression of the vaccine construct in E. coli. Moreover, immune simulation revealed strong antibodies production upon the injection of the designed MEVC resulted in highest peaks of IgM+ IgG production (>3500) between 10 to 15 days. In conclusion the current study provide basis for vaccine designing against the emerging A. xylosoxidans which demands further experimental studies for in vitro and in vivo validations.